Characterization of the sand of Brahmaputra river of Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2012)
The aim of this paper is to study on the mineralogy, morphology, magnetic property and composition of the sand of Brahmaputra River, Bangladesh. The sand has been collected from randomly selected seven places and separated by High Intensity Rolling Magnetic Separator  into three fractions, viz. magnetic, para-magnetic and non-magnetic parts. The identifications of the valuable heavy minerals existing in these fractions have been performed. The valuable heavy minerals in the separated fractions have been counted under reflected and polarizing microscope and it is found that the magnetic fraction contains ilmenite, magnetite and garnet. The major grain size fraction of the magnetic fraction is 125 - 250 ?m (57.18%). Zircon, rutile, xenotime, monazite, sillimanite etc. have been counted in other two fractions. X-ray Diffraction (XRD), X-ray Fluorescence (XRF) and Isodynamic Separator have been applied for mineral assessment and to quantify the relative proportion of mineral species.   DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11448   Bangladesh J. Sci. Ind. Res. 47(2), 167-172, 2012